2012
DOI: 10.1080/1357650x.2011.586701
|View full text |Cite
|
Sign up to set email alerts
|

Lateral organisation in nineteenth-century studio photographs is influenced by the direction of writing: A comparison of Iranian and Spanish photographs

Abstract: The direction of reading has been found to have a significant effect upon aesthetic preference, with left-to-right readers showing a preference for stimuli with a rightward directionality while right-to-left readers prefer stimuli with a leftward directionality. This study looks at a large set of posed, studio photographs to study the cultural interaction between direction of reading and lateral organisation, comparing a corpus of 735 nineteenth-century photographs from Iran (right-to-left reading) with a simi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
29
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 16 publications
3
29
0
Order By: Relevance
“…This has been evident in both naturalistically produced photographs studies and controlled laboratory experiments. For example, González (2012) compared portrait studio photographs taken by Iranian (right-to-left readers) and Spanish (left-to-right readers) photographers in the nineteenth century and demonstrated in line with the above aesthetic studies an overall preference for left-to-right directionality in photographs taken by Spanish photographers, in contrast to a preference for right-to-left photographs taken by Iranian photographers. In a controlled study, Nachson, Argaman, and Luria (1999) examined aesthetic preferences in Russian (left-to-right), Hebrew (right-to-left) and Arabic (right-to-left) participants, presenting them pairs of pictures of human faces and bodies that turned either left or right.…”
Section: Directionality Bias In Aesthetic Judgment Of Pictures or mentioning
confidence: 71%
See 1 more Smart Citation
“…This has been evident in both naturalistically produced photographs studies and controlled laboratory experiments. For example, González (2012) compared portrait studio photographs taken by Iranian (right-to-left readers) and Spanish (left-to-right readers) photographers in the nineteenth century and demonstrated in line with the above aesthetic studies an overall preference for left-to-right directionality in photographs taken by Spanish photographers, in contrast to a preference for right-to-left photographs taken by Iranian photographers. In a controlled study, Nachson, Argaman, and Luria (1999) examined aesthetic preferences in Russian (left-to-right), Hebrew (right-to-left) and Arabic (right-to-left) participants, presenting them pairs of pictures of human faces and bodies that turned either left or right.…”
Section: Directionality Bias In Aesthetic Judgment Of Pictures or mentioning
confidence: 71%
“…Ocklenburg and Güntürkün, 2009) demonstrated that the direction of head-turning in human adults can be associated with handedness or footedness (e.g., Ocklenburg & Güntürkün, 2009) whereas Shaki (2013) found that this can be shaped by cultural spatial habits, such as reading direction. Similarly, some studies found the effect of handedness on directionality bias in aesthetic perception (Banich et al, 1989; Beaumont, 1985; Christman & Dietsch, 1995; Freimuth & Wapner, 1979; Levy, 1976; Mead & McLaughlin, 1992) whereas other studies reported a strong effect of reading habits, with left-to-right readers showing a preference for stimuli with a rightward directionality while right-to-left readers preferred stimuli with a leftward directionality (for details see earlier in this review; Chokron & De Agostini, 2000; Friedrich & Elias, 2016; Friedrich et al, 2014; González, 2012; Ishii et al, 2011; Maass et al, 2007; Nachson et al, 1999). Other studies have further suggested that handedness and reading or writing habits can influence the preferred directionality in an interactive fashion, not only in visual perception but also in drawing figures.…”
Section: A Dynamic Model For the Origins Of Directionality Biases mentioning
confidence: 84%
“…It is important to emphasize that the two accounts are not mutually exclusive, and Pérez González's (2012) data are partially consistent with both. In her corpus, the directionality of photographs of Linear Orderings and Couples was perfectly predicted by RWD.…”
Section: Rwd and The Causes Of The Left-cheek Biasmentioning
confidence: 87%
“…It also generalizes more widely, reaching all kinds of concepts that are correlated with order of mention in language, such as causal relations in agent-patient interactions (Maass & Russo, 2003) or temporal (Ouellet et al, 2010), numerical (Zebian, 2005) and letter (Shaki & Gevers, 2011) sequences. If the pleasantness aroused by visual artistic depictions depends at least partially on their perceived naturalness, this account should also be able to explain the observed effects of script direction on aesthetic preferences (Pérez González, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…RWD is also able to bias the choice of behavioral alternatives (such as study items) from a list (Ariel, Al-Harthy, Was, & Dunlosky, 2011). Even the aesthetic choices of artists, as well as the feelings that are aroused by pieces of visual art, can be affected by RWD (Chokron & De Agostini, 2000;Nachshon, Argaman, & Luria, 1999;Pérez González, 2011).…”
mentioning
confidence: 99%